Exploring barriers to periodontal treatment adherence in patients with periodontitis to inform development of a digital companion: a qualitative study - Weinert, Lina; Sayed, Nihad el; Wensing, Michel; Dannewitz, Bettina; Listl, Stefan (Journal of clinical periodontology, 2025)
Aim The objectives of this study were to gain a comprehensive understanding of patients' barriers to adherence to periodontal treatment and to derive intervention functions for a digital companion to support them through their therapy journey. Materials and Methods A qualitative study incorporating patient and expert interviews was designed. Data were analysed using thematic analysis. Barriers to therapy adherence and functions for a digital intervention were synthesised with the help of the Capability, Opportunity and Motivation behaviour change model. Results Barriers related to periodontal therapy are a lack of awareness of the patients' own responsibility and prioritisation of individual oral health, lack of time to both instruct as well as learn and perform better oral hygiene and lack of knowledge about disease characteristics and ideal habits. Participants expected that a digital intervention should incorporate personalised and comprehensive educational material, possibilities to visually document progress, simple descriptions of oral hygiene tasks, reminders and the inclusion of prompts for self-reflection. Conclusion While a digital health companion has the potential to address the aforementioned barriers, future research should also aim to develop strategies to focus on health systems barriers (e.g., financing and workforce arrangements) as these can influence patient engagement and adherence.
Gesehen am 22.01.2026